The authenticity of digital evidence in proving: A study in the Saudi law of evidence - Alabduljabbar, Zyad Majid (Journal of Economic, Administrative and Legal Sciences, 2022)
Technological development has had a great impact in the emergence of the so-called digital evidence, which has become a question of its authenticity and the extent to which it is considered evidence that can be argued in court; This is because of the problems it faces that threaten to be considered as evidence, and therefore this research came to try to dive into these topics. It began with the definitions of digital evidence, and finding the most appropriate definition. Then analyzed it and clarifying its characteristics and types, then came exposure to the importance of the digital evidence and the obstacles it faces.. The first part concludes with a look at the development of digital evidence rules in the Kingdom of Saudi Arabia Saudi Arabia. In the second part of the research, the discussion will be about the authenticity of the digital evidence, and this is done by researching the Islamic authenticity briefly and then the legal authenticity The researcher reached several results, the most important of which are the differentiation between digital and electronic, the realistic adaptation of the stage the digital evidence is going through, the expansion of the evidence system for the scope of electronic correspondence, and the original authenticity of the digital evidence. The researcher also recommended adding an article in the regulations to define digital evidence clearly and explicitly. He also recommended adding an article in the law of evidence stating that digital evidence should not be used in hudud and retribution crimes, and the establishment of a specialized committee to investigate evidence and ensure its authenticity and freedom from any forgery.